CURRENT PROBLEMS OF ENSURING LOCAL BUDGETARY FINANCIAL STABILITY - Kholmatov Bakhtiyor Abdumutalovich; Usmonov Ahrorjon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article describes the pressing problems of ensuring the financial stability of the local budget in the Republic of Uzbekistan.